A Cube Version of the Square–Diamond Illusion. (January 2021) - Ito, Hiroyuki; Nose, Daichi
The square–diamond illusion is often referred to as a type of size illusion. However, the 45-degree tilting of a square remarkably affects perceived corner angles when a cube version of the figure is used. This illusion is measured and discussed in relation to anisotropy in shape interpretation.